The Portrayal of Moderate Islam Representations in Ms. Marvel (2022) TV Series: English - Anisa Hanifah; Lili Awaludin; Hasbi Assiddiqi (Journal of English Development, 2024)
2022 Marvel released a TV series entitled Ms. Marvel, which shows Kamala Khan, a Pakistani-American woman Muslim who leads as a superheroine. Lives as a minority in Jersey City, Kamala Khan shows her Muslim identity moderately conducive to bear with the society. Therefore, this research aims to describe the representation of moderate Islam in Ms. Marvel (2022) TV series and the influence of those representations on Islam’s stereotypes in the United States media. This research uses descriptive qualitative method through cultural studies approach, that is supported by Stuart Hall’s representation and John Storey’s ideology theories. Furthermore, with the changes of superhero motifs in Ms. Marvel, authors presume that this invention effected to Ms. Marvel’s (2022) TV series popularity by transforming the negative stereotype of Islam into a positive one. The Marvel industry itself prepares minorities, especially Muslim hero performances to attract the entertainment market which is currently dominated by Muslims as the second world’s most adherents. The effect of moderate Islam representations on Ms. Marvel’s popularity is a further plan from this research. In fact, besides Ms. Marvel, another minority issue that is packaged as the core story of Marvel's entertainment production has become a separate marketing strategy for them. Therefore, the result of this research is that moderate Islam representations in Ms. Marvel (2022) TV Series are portrayed in numerous forms and constructs an opposition to Islam’s negative streotypes in the United States media.